Transition moments, radiative transition probabilities, and radiative lifetimes for the band systems A 2Π–X 2Σ+, B 2Σ+–X 2Σ+, and A 2Π–A´ 2Δ of scandium monosulfide, ScS. (May 2018) - Romeu, João Gabriel Farias; Belinassi, Antonio Ricardo; Ornellas, Fernando R.
Highlights: Reliable and accurate potential energy curves for ScS. Most complete characterization of the states X 2 Σ +, A′ 2 Δ, A 2 Π, and B 2 Σ + to date. Transition moments, Einstein Av ´v′′ emission coefficients, and radiative lifetimes. Experimental investigation of the new A′ 2 Δ state should be significantly facilitated. Abstract: A manifold of electronic states of ScS was investigated with special emphasis on the low-lying states X 2 Σ +, A´ 2 Δ, A 2 Π, and B 2 Σ + . For all states, potential energy curves were constructed covering internuclear distances from the equilibrium region through the dissociation limit. For the above states, besides providing the most accurate set of theoretical spectroscopic parameters to date, we have also computed dipole moment functions, transitions dipole moment functions, the associated radiative transition probabilities, and radiative lifetimes. For the states known experimentally, X 2 Σ +, A 2 Π, and B 2 Σ +, our results significantly expand our present knowledge of the energetic profile of these states thus providing a new perspective for understanding the limited spectral data for this species known so far. For the new state, A´ 2 Δ, yet unobserved experimentally, our results are sufficiently reliable and accurate to guide spectroscopists on further studies of this species. Graphical abstracts: